Портмаськись корка: удмурт калык выжыкылъёс / худож. М. Гарипов - Гарипов Менсадык Г. (Удмуртия, 2012)
Экземпляры: Ч/з (20141120) / Инвентарный номер: 101867 / Цена: 145.00 / Авт.знак: П 60 / ГРНТИ: 17.71 / ББК: 82.3(2Рос=Удм)